Case Report: Two Novel L1CAM Mutations in Two Unrelated Chinese Families With X-Linked Hydrocephalus - Zhou, Hang; Yu, Qiuxia; Li, Yingsi; Fu, Fang; Li, Ru; Chen, Guilan; Wang, Dan; Lu, Yan; Yang, Xin; Li, Dongzhi; Liao, Can (Frontiers in Genetics, 2022)
L1 cell adhesion molecule is a type I transmembrane glycoprotein belonging to the immunoglobulin superfamily. Pathogenic mutations of L1CAM can cause L1 syndrome referred to as a variety of disease spectrums characterized by hydrocephalus. In the present study, we reported two novel variants of L1CAM in two unrelated Chinese families with fetal hydrocephalus history. A woman of family 1, with three consecutive adverse birth history of male fetuses with hydrocephalus, was identified by exome sequence with a heterozygous mutation in L1CAM gene, NM_000425.4: c.1696_1703+14del (p. S566Vfs*35), which was predicted to be pathogenic. It is predicted to disrupt RNA splicing and likely leads to an absent or disrupted protein product. In family 2, the mother, previously with once a voluntary termination of pregnancy owning to the fetus with hydrocephalus, was pregnant with fetus with hydrocephalus on her second pregnancy. After fetal blood sampling, a pathogenic deletion of 1511bp in L1CAM, chromosome X: 153131395-153132905(hg19/GRCh37) /NM_000425.4: c.2043_2432-121del1511 leading to deletion of fibronectin type-III repeats I-II., was identified in the fetus with hydrocephalus inherited from his mother by exome sequence. On her third pregnancy, a healthy female fetus was born without the L1CAM variant by preimplantation genetic testing for the monogenic disorder. This study emphasizes the importance of ultrasonic manifestation and family history of fetal hydrocephalus for L1CAM diagnosis. Our study expands the genotypes of L1CAM and aids the genetic counseling of fetal hydrocephalus and even preimplantation genetic testing for the monogenic disorder.